Inequality, Poverty, and Human Capability in Sumatra's Inclusive Growth - Satriawan, Boby; Ratih, Arivina; Setiawan, Dedy (Kirana Publisher (KNPub), 2025)
Inclusive economic growth involves poverty reduction, job creation, income distribution, and the development of agriculture, industry, and social sectors, ensuring equal participation and benefits. This study uses secondary panel data with the Ordinary Least Square (OLS) method and fixed effects across 10 provinces in Sumatra from 2019 to 2023. The analysis shows that development inequality, poverty, and open unemployment negatively impact inclusive growth, where a 1% increase in GINI and PPM reduces IPEI by 4.02% and 3.62%, while an additional Open Unemployment Rate (TPT) decreases IPEI by 2.08%. Conversely, labor force participation and human development positively influence growth, with a one-person increase in AK raising IPEI by 1.22% and a 1% rise in IPM increasing IPEI by 15.03%. Policies for fair economic redistribution are needed through enhanced access to education, healthcare, employment, and empowerment in labor-intensive industries across Sumatra.